STUDY ON IMPROVEMENT FOR THE EXCITATION PERFORMANCE OF BV500 TYPE CONTROLLED SEISMIC SOURCE VIBRATOR PLATE BASED ON TOPOLOGY OPTIMIZATION METHOD - HUANG Zhiqiang; FU Mingwei; XI Yuxi; LI Gang; WANG Ruohao; PU Wei (Jixie qiangdu)
During the operation of the BV500 type controlled seismic source vibrator in Sichuan and Chongqing areas, due to the improper plate design, the vibration energy down-transfer rate is low and the excitation signal distortion is serious.Therefore, the continuum topology optimization method was introduced, and a variable density method of the solid isotropic material with penalization (SIMP) model was used to optimize the design of BV500 controlled seismic source vibrator plate from two aspects — reducing mass and increasing stiffness, and an “octagonal I-steel-20a” plate was innovatively developed.After optimization, the mass of the plate was reduced by 45.29%, and the stiffness of the plate was increased by 79.92%, the vibration performance of the plate before and after optimization is studied.The simulation results show that compared with the original aluminum alloy plate, the energy down-transfer rate of the “octagonal I-steel-20a” plate increases by 15.11%，the displacement amplitude of the ground surface contact center point increases by 43.74%, and the amplitude of the interaction force increases by 40.56%.The field experiment shows that when the “octagonal I-beam-20a” plate is excited, the effective value of the average vibration velocity of the near-field signal of the detector is increased by 22.23%, and the effective value of the average vibration velocity of the far-field signal of the detector is increased by 39%, the law is consistent with the numerical simulation conclusion of controlled seismic source road excitation.The excitation performance of the “octagonal I-beam-20a” plate is better than that of the original aluminum alloy integral plate, which effectively improves the road excitation effect of BV500 type controlled seismic source in Sichuan and Chongqing areas.